Quo vadis regulador? Uma análise das trajetórias profissionais e políticas dos reguladores estaduais no Brasil. - Santos, Aline de Menezes (2014)
Independent regulatory agencies (IRAs) were established to regulate public services and economic and social sectors, in three levels of government. Provided with decision-making, administrative and financial autonomy, with fixed terms for its leaders and not identical to the Executive, have an 'identity' itself to ensure the independence inherent to the regulatory activity. Assuming that the quality of regulations depends on the quality of regulators, key decision-making borrowers under the regulatory agencies, the present study sought to understand some important aspects related to autonomy as it is manifested in practice: expertise levels of regulators and the dynamic capture them. To this purpose, a database containing information on state regulators was built, highlighting features related to the IRAs and individual characteristics of regulators from graduation, previous experience and postgraduate courses, conduction and mandate renewals, until placement professional postoffice. The analysis, descriptive, indicates that nearly 50% of state regulators are engineers and economists, the rest being distributed among various professions, especially the area of law, indicating a legalistic tradition in Brazilian IRAs, as well as many of the listed to take over as leader confirms previous experience in the regulated sector. However, the expertise differs according to the region of the country and the type of regulatory agency, being lower in the northern and largest region in the southeast, also dominated more specialized agencies. Also it notes a tendency to create a regulocratas network: regulators that stand out for a professional trajectory between agencies. When data are looked at from the capture theories, it is emphasized that, unlike the US regulators, most state regulators remains in the public sector after leaving the executive board. The party conduction and renewals indicate predominance of parties as PSDB and PMDB, however it is perceived that renewals take place independent of party power, indicating the strength of the Brazilian model